A review of the American species of Xenelmis Hinton (Coleoptera: Elmidae), with a new species from Argentina - Manzo, Verónica (Zootaxa, 2006)
The genus Xenelmis Hinton is taxonomically reviewed. A new species of riffle beetle from Argentina, Xenelmis uruzuensis sp. nov. is described and illustrated from adults of both sexes and the larva. Ten additional species of Xenelmis are treated: X. sandersoni Brown, X. bufo (Sharp), X. rufipes Delève, X. leechi Perkins & Steiner, X. marcapata Perkins & Steiner, X. tarsalis Hinton, X. teres Hinton, X. audax Hinton, X. comis Hinton and X. laura Brown. Male genitalia of each species are illustrated, some of them for the first time. Distributional records, diagnoses and a key to distinguish the species of Xenelmis are included.